Effect of 2, 4-Thiazolidinedione on Limousin Cattle Growth and on Muscle and Adipose Tissue Metabolism. (6th December 2012) - Arévalo-Turrubiarte, M.; González-Dávalos, L.; Yabuta, A.; Garza, J. D.; Dávalos, J. L.; Mora, O.; Shimada, A.
Abstract : The main adipogenic transcription factor PPARγ possesses high affinity to 2, 4-TZD, a member of the Thiazolidinedione family of insulin-sensitizing compounds used as adipogenic agents. We evaluated 2, 4-TZD's effect on bovine growth and PPAR tissue expression. Seventeen Limousin bulls (18 month-old; 350 kg body weight (BW)) were assigned into 2 treatments: control and 2, 4-TZD (8 mg/70 kg BW) and were fed until bulls reached 500 kg BW. They were weighed and their blood was sampled. DNA, RNA, and protein were determined in liver; skeletal muscle; subcutaneous (SC), omental, perirenal adipose tissues (AT) to determine protein synthesis rate and cellular size. Expression of PPAR mRNA was measured in liver and muscle (PPARα, -δ, and -γ ) and SC adipose tissue (γ ) by real-time PCR. No significant differences were found (P > 0.1 ) in weight gain, days on feed, and carcass quality. Muscle synthesis was greater in controls (P < 0.05 ); cell size was larger with 2, 4-TZD (P < 0.05 ). PPARα, -δ, and -γ expressions with 2, 4-TZD in liver were lower (P < 0.01 ) than in muscle. No differences were found for PPAR γ mRNA expression in SCAT. The results suggest the potential use of 2, 4-TZD in beef cattle diets, because it improves AT differentiation, liver, and muscle fatty acid oxidation that, therefore, might improve energy efficiency.